AN EXAMINATION OF THE TRENDS AND FACTORS RESPONSIBLE FOR CHALLENGES FACING MUSLIMS IN TARABA STATES, NIERIA (1991-2021) - Ali, Bello (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
The objective of this study was to thoroughly examine the trends and factors contributing to the challenges experienced by Muslims in Taraba State. Primary and secondary data were collected through structured interviews, participatory observation, and analysis of documentary sources. Several significant findings emerged from the study. It was observed that there was a harmonious relationship between Muslims and non-Muslims in the past, with Muslims enjoying a high socio-political and economic status that was respected by non-Muslims. However, the study identified various challenges faced by Muslims in Taraba State. These challenges included disunity, a lack of control over political power in the state, internal divisions, the flawed approach of certain early scholars, and moral decline among Muslims. Additionally, challenges such as ethnic identity, indigene and minority issues, unfavorable government policies, and the proliferation of intensive Fulbe-Hausa Christian evangelistic activities targeting Fulbe and Hausa Muslim populations were identified. The study also revealed several factors responsible for these challenges, including the lukewarm attitudes of some Muslim leaders, low levels of education in both Islamic and Western education, the failure of Muslim politicians and elites to unite for the advancement of Islam and Muslims, the breakdown of family institutions, and the absence of a sustainable financial foundation for Da'wah funding. In conclusion, the study provides recommendations for overcoming these challenges and improving the situation for Muslims in the state.